Perceptions Versus Reality of QAnon Radicalization: A Comparative Study - Brett Burton; Sophia Moskalenko (Journal for Deradicalization, 2023)
The online following of conspiracy theory believers known as QAnon has recently come into focus of U.S. government agencies and terrorism scholars, raising questions about the risk of violence it poses. To address these questions, as well as to triangulate existing research on QAnon’s threat, the present study compared survey responses about actual radical intention and activist intention scores of QAnon supporters (n = 113) and non-QAnon participants (n = 287), relative to QAnon’s radicalization as perceived by non-QAnon participants. Actual radical intention scores for QAnon supporters were significantly lower than the perceptions of QAnon radical intentions, and were not significantly different than the actual radical intention scores for non-QAnon participants. Activist intention scores were lowest among QAnon supporters, followed by non-QAnon supporters, and then by perceptions of QAnon activist intentions. The implications of the results for public policy are discussed.